PATHOLOGICAL CHANGES IN THE INNER EAR IN EXPERIMENTAL MODELING OF SENSORINEURAL HEARING LOSS IN ANIMALS - V. G. OVSYANNIKOV; T. V. ZOLOTOVA; E. V. LOBZINA; N. V. DUBINSKAYA (Кубанский научный медицинский вестник, 2018)
Aim. Study of pathological changes in the inner ear in the modeling of sensorineural hearing loss in laboratory animals.Materials and methods. A pilot study involving 27 laboratory animals − white outbred rats – was conducted. Modeling of sensorineural hearing loss was conducted by exposing them for 10 days to broadband noise of 90 dB, vibration and simultaneous immobilization of laboratory animals divided into 3 groups according to exposure conditions. The development of hearing loss was confirmed by the results of the registration of delayed caused emissions and emissions at the frequency of distortion products. After removing rats from the experiment histological medication from animals cochlear was produced and they were studied by the method of light microscopy.Results. In animals exposed to noise and vibration effects on the background of immobilization, the formation of persistent sensorineural hearing loss was achieved, which was confirmed by objective registration of violations of auditory function, and also by the results of morphological study of cochlear of the temporal bones of animals. More pronounced histological changes were noted in animals exposed to noise and vibration on the background of immobilization compared with the group of rats which were exposed only to noise impact and immobilization without applying vibration. Dystrophic and destructive changes in the structures of the spiral organ, signs of apoptotic way of cell death in the inner ear were detected. In addition, pronounced changes occurred in the spiral ganglia.Conclusion. Modeling of sensorineural hearing loss in laboratory animals on the basis of noise and vibration exposure in terms of immobilization leads to the formation of persistent sensorineural hearing loss, as evidenced by functional and morphological methods. Pathological changes in the inner ear show themselves through dystrophic and destructive changes in the spiral organ, including apoptosis of cells, and especially in the spiral ganglia. The use of this noise-vibration model of hearing loss can be a promising basis for future studies of drugs for the treatment of sensorineural hearing loss.